Anger rumination, binge eating, and at‐risk alcohol use in a university sample. (20th October 2017) - Wakeford, Gillian; Kannis‐Dymand, Lee; Statham, Dixie
Abstract: Objective: Binge eating and alcohol consumption have been associated with attempts to reduce negative affect such as anger. Anger rumination has been associated with maintaining anger. The aim of the current study was to explore the association between anger rumination and binge eating and at‐risk alcohol use. Method: Participants were 563 university students aged between 18 and 66 years who completed an online survey containing the Anger Rumination Scale (ARS), Eating Disorder Diagnosis Scale (EDDS), Alcohol Use Disorders Identification Test—Consumption (AUDIT‐C) and Depression, Anxiety, & Stress Scale (DASS‐21). Results: The results showed that individuals who endorsed elevated levels of binge eating behaviour had increased levels of anger rumination, specifically angry afterthoughts and angry memories, compared to healthy controls. In contrast, individuals who engaged in at‐risk alcohol use without binge eating did not report significantly increased levels of anger rumination. Conclusions: This study highlights anger rumination as a potential factor in maintaining binge eating behaviour and suggests that screening for and addressing anger rumination may be an important component of psychological treatment.